Quantum Cascade Laser Spectroscopy: Developments and Applications - Walker, RJ (2011)
This thesis presents work examining the characteristics and applicability of quantum cascade lasers. An introduction is given explaining both the desire for a widely tunable, narrow bandwidth device working in the midinfrared, as well as detailing the ways in which quantum cascade lasers (QCLs) fulfill these requirements. The development and manufacture of QCLs are then discussed. The experimental section of this thesis is then split into three parts. Chapter 2 concerns the characterisation and application of several pulsed QCLs. The intrapulse mode of operation is employed and the effect of the resulting rapid frequency chirp upon molecular spectra is investigated in the form of rapid passage signals. The evolution of said rapid passage signals is then investigated as a function of chromophore pressure and identity, with different QCLs, chirp rates, and optical path lengths. The prospect of producing population transfer with chirped lasers is discussed. Chapters 3, 4, and 5 are then concerned with the application and characterisation of continuous wave QCLs. In these chapters a widely tunable commercially produced EC-QCL is utilised as well as two DFB QCLs, one of which is used in tandem with a home-made mount and temperature controller. In Chapter 3 a number of sensitive detection techniques are compared with the employment of wavelength modulation spectroscopy, long path cells and optical cavities, and the narrow bandwidth of QCLs utilised to determine a previously unknown spectral constant of DBr. Chapters 4 and 5 then utilise the high power of an external cavity quantum cascade laser in sub-Doppler Lamb-dip and polarisation spectroscopy measurements and then a pump-probe experiment. The laser linewidth is investigated on a millisecond timescale returning a current noise limited value of c.a. 2 MHz and the fundamental linewidth of the device investigated by altering the injection current. Chapter 5 is concerned with the pump-probe experiment, directly measuring the hot band absorption in a ladder like transition (R(6.5)$_\frac{1}{2}$ $v=1←0$ and P(7.5)$_\frac{1}{2}$ $v=1←0$). The Bennett peak in the hot band is observed with a DFB-QCL swept at $\sim 0.15$ MHz ns$^{-1}$ and is seen not just as a pump bandwidth limited lineshape, but as a highly velocity selected rapid passage signal. The effect of pressure, pump and probe scan rate and power upon this rapid passage signal is also studied. It is further noted that rapid thermalisation occurs within $v=1$ such that at pressures above c.a. 30 mTorr a broad NO doublet absorption is observed beneath the Bennett peak from which a total population transfer of c.a. $16 %$ can be estimated. Finally an experiment is discussed in which this population transfer could be increased for use in secondary applications. Chapter 6 then presents initial measurements with two prototype pulsed 3.3 \si{\micro\metre} QCLs considering the prospects of such devices. A Fabry-Pérot device is first studied using a Fourier transform spectrometer and temperature tuning used to produce a spectrum of the Q-branch of CH$_4$ around 3025 cm$^{-1}$. Experiments are then performed using a DFB QCL investigating the chirp rate of the system as an indicator of the rate of heat accumulation within the system. Heat management is of particular consideration when the sea-change is made from pulsed to continuous devices. For this device absorption spectra of two CH$_4$ transitions at 2971 cm$^{-1}$ are used to determine the chirp rate, which is found to be c.a. 1.8 GHz ns$^{-1}$, at least an order of magnitude higher than that of the longer wavelength pulsed devices considered in Chapter 2.